The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/j.1365-2559.2013.04352.x
|View full text |Cite
|
Sign up to set email alerts
|

Signet‐ring cell change in adenoid cystic carcinoma: a clinicopathological and immunohistochemical study of four cases

Abstract: ACC-SRC is a non-mucin-producing and non-lipid-producing phenomenon, possibly related to disturbed differentiation of ductal/luminal cells. This cellular modification in ACC apparently does not change the biological behaviour of the tumour, but it may cause significant diagnostic problems, particularly in incisional biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…15 PDC cases carried more complex genotypes, and in addition, they showed a more adverse clinical behavior. This finding supports the idea that classical ACC can undergo transformation into adenocarcinomas with variable degrees of differentiation, or even to other histological types, 41 which are not always high-grade, contributing to the controversy related to this phenomenon.…”
Section: Discussionsupporting
confidence: 84%
“…15 PDC cases carried more complex genotypes, and in addition, they showed a more adverse clinical behavior. This finding supports the idea that classical ACC can undergo transformation into adenocarcinomas with variable degrees of differentiation, or even to other histological types, 41 which are not always high-grade, contributing to the controversy related to this phenomenon.…”
Section: Discussionsupporting
confidence: 84%
“…As we have found that inflammation appears to be responsible for an increase Myb expression during early events of CRC, for example, ACF and adenoma formation (Pereira et al , in press) prior to detectable mutated Myb regulatory sequences we decided to activate Myb in the initiation phase of CRC. MybER mice were treated with tamoxifen over a period of 8 weeks, six of which also employed weekly colon carcinogen azoxymethane (AOM) injections 26 ( Figure 3d ). Hence, MybER was activated for 2 weeks prior to AOM-treatment to allow the expansion of the ISC pool.…”
Section: Resultsmentioning
confidence: 99%
“…MybER transgenic mice were backcrossed onto a C57/BL6 background and experiments were conducted between generations 2–8 and used to generate compound p27 ± :MybER 53 and Apc min/+ :MybER 54 mice approved by the PMCC Animal Ethic Committee. Mice were fed Tamoxifen-chow (1 g Kg −1 ) for 2 weeks prior to the start of AOM intraperitoeal injections (10 mg Kg −1 body weight) once weekly over 6 consecutive weeks 26 during which mice were provided with tamoxifen.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent to the description of SRCA, other primary salivary tumor types such as salivary duct carcinoma [3] and adenoid cystic carcinoma [4] have been described with signet ring cell components. Additionally, the recently described mammary analog secretory carcinoma (MASC) may show a mucin rich vacuolated appearance resembling SRCA [5].…”
Section: Introductionmentioning
confidence: 99%